If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(5 + 6x) + -1(5x + 6) * 7 = 3 (5 * 6 + 6x * 6) + -1(5x + 6) * 7 = 3 (30 + 36x) + -1(5x + 6) * 7 = 3 Reorder the terms: 30 + 36x + -1(6 + 5x) * 7 = 3 Reorder the terms for easier multiplication: 30 + 36x + -1 * 7(6 + 5x) = 3 Multiply -1 * 7 30 + 36x + -7(6 + 5x) = 3 30 + 36x + (6 * -7 + 5x * -7) = 3 30 + 36x + (-42 + -35x) = 3 Reorder the terms: 30 + -42 + 36x + -35x = 3 Combine like terms: 30 + -42 = -12 -12 + 36x + -35x = 3 Combine like terms: 36x + -35x = 1x -12 + 1x = 3 Solving -12 + 1x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 1x = 3 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = 3 + 12 1x = 3 + 12 Combine like terms: 3 + 12 = 15 1x = 15 Divide each side by '1'. x = 15 Simplifying x = 15
| 19-(9d-5)+18d=3(6d+5) | | x/12=60 | | 6(v+4)-2v=2(2v+4)-14 | | Y/6=5/4 | | 9x+5-2x=-4x-14+x | | i-8=3 | | (3y-8)(-6y^2+8y+2)= | | x^2-x+16=6x-4 | | -.50/2.25 | | s=4/7 | | 6x^2-2x+6=5x^2+10x | | (16)^(-3/4) | | .14=.06+.75x | | 0.5x^2+12=5x | | (x+3)(y-5)=450 | | -3(4x-6)+9=-12x+27 | | y=-7(3/2)^x | | 5x(4-6)=19x-7 | | 4/7 | | 14-3t+7t=15+3t-16 | | 4f-5/3=k | | 2x(4x-3)=8x(2-18) | | 18/0.33 | | 7ab+14a= | | -10*(-10+9)4thpower= | | -3+2t=3(t+3) | | -2y=42 | | -7(7c-6)+8(7c-1)=-c+9(c+10) | | 11=y/5-11 | | 15=y/7 | | c=200+0.8y | | 4-x/140x |